The genus Sebastes Cuvier, 1829 (Pisces, Scorpaenidae) in the North Atlantic: species and stock discrimination using traditional and geometric morphometrics - Garabana, Dolores (Universidad de Vigo, 2005)
307 páginas European Union programme QLK5-CT1999-01222 Peer reviewed